A synopsis of the mental health concerns of university students: results of a text-based online survey from one Australian university - Wynaden, Dianne; Wichmann, Helen; Murray, Sean (Routledge, 2013)
Within the university community, student demographic data highlights a high level of cultural diversity and an ‘at-risk’ population for the onset of mental health problems. Moreover, the transition to higher education is itself associated with a range of emotional, social and academic demands that can cause psychological distress. Therefore, at any one time, a substantial number of students may be attempting to complete university studies while managing problematic symptoms, behaviours or an emerging or diagnosed mental disorder. The aim of this paper is to provide a snapshot of these students' experiences to enable strategic planning of future university support services. Of particular importance was the identification of facilitators and barriers that this group of students faced while engaged in university life. Participants were 1378 students enrolled at a Western Australian university who accessed a text-based online survey during May 2009. The students provided descriptions of the range of problematic symptoms, behaviours and/or disorders that were causing interference with their lives, and university career. Not surprisingly, the most commonly identified disorders with the participant population were depression, anxiety and stress-related concerns. More than half the sample had not sought professional help. The results highlight the fact that universities are well placed to play a major role in improving pathways to primary care and early intervention for students with an emerging or diagnosed mental health problem and to identify and support students trying to manage the ‘normal’ psychological demands associated with higher education.